Implications of aromatic–aromatic interactions: From protein structures to peptide models. (7th October 2015) - Madhusudan Makwana, Kamlesh; Mahalakshmi, Radhakrishnan
Abstract: With increasing structural information on proteins, the opportunity to understand physical forces governing protein folding is also expanding. One of the significant non‐covalent forces between the protein side chains is aromatic–aromatic interactions. Aromatic interactions have been widely exploited and thoroughly investigated in the context of folding, stability, molecular recognition, and self‐assembly processes. Through this review, we discuss the contribution of aromatic interactions to the activity and stability of thermophilic, mesophilic, and psychrophilic proteins. Being hydrophobic, aromatic amino acids tend to reside in the protein hydrophobic interior or transmembrane segments of proteins. In such positions, it can play a diverse role in soluble and membrane proteins, and in α‐helix and β‐sheet stabilization. We also highlight here some excellent investigations made using peptide models and several approaches involving aryl–aryl interactions, as an increasingly popular strategy in protein and peptide engineering. A recent survey described the existence of aromatic clusters (trimer, tetramer, pentamer, and higher order assemblies), revealing the self‐associating property of aryl groups, even in folded protein structures. The application of this self‐assembly of aromatics in the generation of modern bionanomaterials is also discussed.